Thrombin Binding Aptamer, More than a Simple Aptamer: Chemically Modified Derivatives and Biomedical Applications - Avino, Anna; Fabrega, Carme; Tintore, Maria; Eritja, Ramon (Current Pharmaceutical Design, 2012)
The thrombin binding aptamer (TBA) is a well characterized chair-like, antiparallel quadruplex structure that binds specifically to thrombin at nanomolar concentrations and therefore it has interesting anticoagulant properties. In this article we review the research involved in the development of new TBA derivatives with improved anticoagulant properties as well as the use of the TBA as a model compound for the study of quadruplex structures. Specifically, we describe the impact of modified nucleosides and non-natural backbones in the guanine tetrads or in the loops and the introduction of pendant groups at the 3' or 5'-ends. The modified oligonucleotides are shown to be excellent tools for the understanding of the molecular structure of the TBA and its folding properties. Finally, we review the use of the TBA-Thrombin recognition system for the development of analytical tools based on the TBA folding.
Keywords: oligonucleotide synthesis